Farmer digital expert assistance systems - Samsuri, Fahmi B.; Narayanamurthy, Vigneswaran; Ranganathan, Balu (2016)
In this proposed idea a global positioning system (GPS) based farmer digital assistant (FDA) is suggested which is capable of analysing the agricultural field and environmental factors associated with the field. The agricultural yield to be harvested depends on the liquidity content of the soil, mineral content of the soil, geographical position of the field, microbial content of the soil and temperature of the environment. The other parameters include irrigation, spraying of chemicals, animals or intruders getting into the field, etc. The embedded system proposed here monitors all these parameters and provides the appropriate values and suggestions to the farmer to attain the sustainable yield. The GPS system module when placed in the field of interest gathers the longitude and latitude values of the location of the field. The location is then compared with the existing databases say soil maps and provides the nature and type of crop to be cultivated with all specifications to obtain maximum yield at that location. Once the nature of crop for cultivation for particular period of time is chosen by matching the geographical characteristics of the field, the proposed system provides the complete list of specification and tasks to be done to obtain high quality food product with maximum yield. To make it happen several factors as mentioned are monitored using set of sensors. The temperature of the field environment is monitored using temperature sensor of high precision and accuracy. The innate liquid content of the soil is determined by the liquidity sensor and it provides the amount of water content to be irrigated to the field for sustainable usage of water source. Series of chemical sensors will be placed in the designed module which will monitor the concentration of the mineral content in the soil and will display the amount of insecticides, pesticides and fertilizers to be sprayed, within the permissive limits, to the field to obtain healthy yield. The microbe concentration and their activities in the field are monitored using gas sensor which monitors the concentration of the gas in the field and infers the nature of microbes present. Finally there will also be a camera employed to continuously monitor intruders and animals getting into the field and if detected alerts the farmer. All the above discussed sensor outputs and system can be integrated with a GSM modem which will send alert messages as SMS or IVRS recorded call alerts in region specific languages to farmer and representatives when required.